Financial position analysis of agricultural enterprises in Republic of Srpska - Stojanović Tamara; Stojanović Stevica (Agroznanje, 2015)
This text focuses on the most important indicators of financial position such as financial balance (liquidity), indebtedness and solvency. Since 72% of total enterprises of agricultural industry in Republic of Srpska has no short-term liquidity, 68% of them has no long-term liquidity, 63% of enterprises has more than 50% of financial sources financed through debt, and 66% of them is insolvent from the banking sector point of view, it can be concluded that majority of agricultural companies' financial position is between acceptable and bad. Although this analysis does not include farms which are main pillars of agricultural production in Republic of Srpska, the suboptimal financial position of majority of agricultural companies in Republic of Srpska indicates that the whole industry has financial problems and needs systematic measures for overcoming the causes of such position and improving not only financial but the whole economic position of agriculture as industry.